A prorrogação por interesse público das concessões de serviço público - Guimarães, Felipe Montenegro Viviani (2018)
This dissertation deals with the prorogation of the term of validity of the public service concession contracts for reasons of convenience and opportunity of the Granting Authority (or, simply, prorogation by public interest). It is justified, among other reasons, because several normative acts have been issued recently in Brazil authorizing the prorogation by public interest of many concession contracts, so that the theoretical and practical interest in the subject is very great in our Country, at this moment. Thus, this dissertation aims to verify whether the prorogation by public interest is compatible with the concept of prorogation constant of the Constitution of the Federative Republic of Brazil of 1988 ("CRFB/88") and, if so, to present its main aspects. The research hypothesis is that this spicies of prorogation is compatible with the Brazilian Constitution. The method of approach of the subject is the deductive, and the method of research, the bibliographic. Finally, the main conclusion of the present study is that the prorogation by public interest (common or anticipated, with or without premial character) is compatible with CRFB/88, being subject, however, to different requirements, conditions and limits to be fulfilled legitimately